Hubungan Kepuasan Perolehan Layanan Bimbingan dan Konseling dengan Kedisiplinan Menaati Tata Tertib Sekolah pada Siswa Kelas VIII di SMP Negeri 2 Atambua - Bau, Yovita Yanti; Geradus, Uda; Indrawan, Putu Agus (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2023)
This study aims to determine: (1) Description of the Satisfaction of Receiving Counseling Services, (2) An Overview of Discipline Students, (3) The Relationship between Satisfaction. This study uses a quantitative. This research was conducted at SMP Negeri 2 Atambua with a sample of 78 students using stratified random technique. The data collection technique is a questionnaire. The data analysis technique is descriptive analysis and correlation analysis with the help of SPSS for Windows 22.00 Version. The results showed that 60 students (76.92%) of SMP Negeri 2 Atambua were satisfied with obtaining counseling services, and 57 students (73.07%) were disciplined in obeying school rules. There is a positive relationship between satisfaction with obtaining counseling services and discipline in obeying school rules with an rxy value of 0.343. The results of the correlation significance test show that there is a positive relationship with the value of r count > r table, namely 0.343 > 0.2227. Therefore, students have satisfaction such as obeying the rules that apply at school and the ability to show attitudes, behavior at school